2020
DOI: 10.1080/02619768.2020.1803272
|View full text |Cite
|
Sign up to set email alerts
|

Learning from professional challenges identified by school and institute-based teacher educators within the context of school–university partnership

Abstract: Over the last decade, in both the Netherlands and England, there have been national policydriven changes to establish school-based teacher education where the focus is on increased responsibility for schools in initial teacher education. In this research stories were gathered of challenges experienced 'on the ground' by teacher educators in these school-university partnerships. The aim was to explore the reality of working within partnerships for schoolbased teacher education rather than a comparative study be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The success of the training process lies in a strong partnership of knowledge, processes and people, especially the mentor teachers (Ingersoll & Strong, 2011; Orland‐Barak & Wang, 2021). In the clinical model, all these take place with an emphasis on the academia‐field connection and on the processes that occur between them as a product of full partnership (Beshir et al., 2023; Straub & Ehmke, 2021; White et al., 2022). Furthermore, as for the role of the principal of the training school, it seems that in the clinical field‐focused model, the principals need to be in constant contact with the teacher students and constitute a significant figure for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the training process lies in a strong partnership of knowledge, processes and people, especially the mentor teachers (Ingersoll & Strong, 2011; Orland‐Barak & Wang, 2021). In the clinical model, all these take place with an emphasis on the academia‐field connection and on the processes that occur between them as a product of full partnership (Beshir et al., 2023; Straub & Ehmke, 2021; White et al., 2022). Furthermore, as for the role of the principal of the training school, it seems that in the clinical field‐focused model, the principals need to be in constant contact with the teacher students and constitute a significant figure for them.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, academia-field partnerships have strengthened in various fields, including teacher education (Straub & Ehmke, 2021;White et al, 2022). Studies show that how pre-service teachers (student teachers) learn in the field is critical to their future success (Goldrick et al, 2012;Inbar-Lourie & Haim, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, teacher agency has been increasingly studied (Biesta and Tedder, 2007;Ollerhead, 2010;Priestley et al, 2012Priestley et al, , 2015Oolbekkink-Marchand et al, 2017;Tao and Gao, 2017;Bergh and Wahlström, 2018;Jenkins, 2020;Martin, 2020;Ashton, 2021;Huang, 2021;Huang and Yip, 2021). Those results have revealed that teacher agency is an influential factor for teacher professional learning, teaching innovation, school improvement and sustainable educational change (Deters, 2011;Feryok, 2012;Toom et al, 2015;Tao and Gao, 2017;Miller and Gkonou, 2018;Weng et al, 2019;Huang, 2021;Ashton, 2022;White et al, 2022). More studies (see Ng and Boucher-Yip, 2016;Kayi-Aydar, 2019) have been conducted to examine either how researchers adopt relevant theoretical frameworks and research methods in quest of understanding language teacher agency, or explore language teacher agency across interdisciplinary perspectives, for instance, to understand how teachers respond to top-down English language planning and policy decisions.…”
Section: Introductionmentioning
confidence: 99%